2020
DOI: 10.37398/jsr.2020.640118
|View full text |Cite
|
Sign up to set email alerts
|

Screening for Endophytic Fungi with Antibacterial Efficiency from Moringa Oleifera and Withania Somnifera

Abstract: Plants have a great potential to grow while carrying inside them fungi and bacteria known as endophytes. These endophytes have a potential to produce bioactive molecules which are of immense pharmaceutical importance. In the current study, plants having medicinal properties such as Moringa oleifera and Withania somnifera were explored for studying endophytic fungi associated with them. Moringa oleifera and Withania somnifera are widely known for their nutritional and medicinal values. The endophytic fungal ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…were isolated and identified from the root of W. somnifera with the colonization frequency of 35% [ 95 ]. Atri et al [ 96 ] isolated twenty-four fungal endophytes from W. somnifera during the rainy season of which ten isolates from the stem with the highest colonization frequency (CF) of 41.66% followed by nine from the root with 37.50% CF and five isolates from the leaf with 20.83% CF. Among them, two fungal isolates were identified as Alternaria sp.…”
Section: Endomicrobial Diversity Of Important Medicinal Plants/genusmentioning
confidence: 99%
See 3 more Smart Citations
“…were isolated and identified from the root of W. somnifera with the colonization frequency of 35% [ 95 ]. Atri et al [ 96 ] isolated twenty-four fungal endophytes from W. somnifera during the rainy season of which ten isolates from the stem with the highest colonization frequency (CF) of 41.66% followed by nine from the root with 37.50% CF and five isolates from the leaf with 20.83% CF. Among them, two fungal isolates were identified as Alternaria sp.…”
Section: Endomicrobial Diversity Of Important Medicinal Plants/genusmentioning
confidence: 99%
“…In addition to this, an endophytic fungus C. globosum also reported from M. oleifera with good antimicrobial activity against some resistant clinical isolates [ 132 ]. Atri et al [ 96 ] reported a total of twenty-one endophytes in their study among them four potent isolates were identified as Colletotrichum sp., Cladosporium sp., and Fusarium sp. Moreover, Mwanga et al [ 133 ] have isolated two fungal endophytes namely Nigrospora sp.…”
Section: Endomicrobial Diversity Of Important Medicinal Plants/genusmentioning
confidence: 99%
See 2 more Smart Citations
“…In case of M. olifera , recent studies by Kaur et al ( 2020 ), Arora and Kaur ( 2019 ) have described the isolation of Aspergillus fumigatus , an endophytic fungus that possessed antimicrobial potential against prominent pathogens including methicillin-resistant Staphylococcus aureus (MRSA). Another recent study by Atri et al ( 2020 ) reported the isolation of other fungal species such as Fusarium sp., Colletotrichum sp., Cladosporium sp. and Alternaria sp.…”
Section: Endophytesmentioning
confidence: 99%